The design of flexible front end framework for accessing patient health records through short message service - Abd Ghani, Mohd Khanapi; Bali, Rajeev K.; Naguib, Raouf N.G.; Marshall, Ian M.; Shibghatullah, Abdul Samad (2007)
Seamless access to a patient’s lifetime health records is crucial for helping doctors in making decision for providing accurate treatment and continuous care. It is equally crucial in the situation where patients freely visit any healthcare facility for the same medical problem, and can be referred to the appropriate hospital anywhere in the country. Without seamless and continuous capability, the patient health records cannot be accessed timely, accurately and completely. Patients may have to perform repetitive tests and exams even though they may have historically suffered from the same disease. This paper proposes flexible front-end framework to upkeep a patient’s health records continuously and seamlessly using portable devices such as laptops and mobile phones and the Global System for Mobile and Short Message Service.